Analisis implementasi program sekolah sehat dalam membangun karakter peduli lingkungan di sekolah dasar - Harisyah Khoirin Aminah; Sukarno Sukarno; Septi Yulisetiani (Didaktika Dwija Indria, 2022)
Abstract. The background of this study aims to make students have the character of caring for the environment and Clean and Healthy Life Behavior so as to create a conducive environment through healthy school programs. This study employs the descriptive qualitative case study research method. School principals, sports teachers, UKS administrators, and minor medical students were the study's participants. Interviews, observation, and documentation are used to collect data. The source and technique triangulation technique is used in the validation test. The data analysis technique using interactive has three stages: data reduction, data display, and making conclusions. The UKS Trias, that include health education, health services, and environmental development, guide the findings of the research on the implementation of the healthy school program. Communication, resources, disposition, and bureaucratic structure are used in the implementation of the healthy school program. Infrastructure is complete, there is solid support, there is financial assistance, and there is assistance for replanting land. According to the school's eco friendly policy, namely: routine habits, spontaneous actions, exemplary, and conditioning, the results of the research on the implementation of the healthy school program in building the character of caring for the environment were successful.